Die Freiheit der Kirche bei A. Rosmini: Rosminis Ansatz zur Reform des kirchlichen Selbstverständnisses - Krienke, Markus (Zeitschrift für katholische Theologie, 2003)
Unlike many protagonists of a "liberal catholicism", the Italian theologian and philosopher Antonio Rosmini founds his claim for the liberty of church on his anthropology. He connects this with Claims for ecclesiological reforms. Based on his knowledge of biblical and patristic theology, he suggests in his most famous work "The five wounds of the church" some ideas, which were taken up during the Second Vatican Council. In his "philosophy of right" he describes the relation between church, State and society with the aid of his anthropology as "subsistent right". With this "anthropological turn" as the basis of the church's selfdetermination he suggests already in the first half of the 19th Century a view of the relation between church and State which became theologically influential only in the second half of the 20th Century.